Relationship between Personality Traits and Aggression among Online Video Gamers - Sajid Mahmood Alvi; Sadia Asghar; Saqib Younas Alvi (Journal of Management Practices, Humanities and Social Sciences, 2023)
People of all sexes and age groups can find entertainment in playing online games. They play video games for entertainment, but too much gaming can result in addiction. Both beneficial and adverse psychological impacts can be attributed to gaming, but the adverse effects outweigh the positive effects significantly. The current study looked at the association between aggressiveness and personality traits among PUBG players who were university students. Buss Perry Aggression questionnaire with an alpha reliability of .78 and the Big five inventory with an alpha reliability of .63 were used to collect the data. The research was carried out using a cross-sectional research approach. Research data was gathered using the survey approach using the convenience sampling technique and data was collected through a google form. The number of PUBG players in the sample was 250. Correlation, t-test, and regression analysis were used to compute the results. It was hypothesized that males would be more aggressive than females. The results suggest that aggression differs significantly by gender. The findings a positive association between personality qualities and aggression (openness, conscientiousness, agreeableness, neuroticism, and extraversion). These results contribute to our understanding of the psychological impact on online video game players. The study's findings aid in resolving the PUBG player’s psychological issues. Although the field has rapidly expanded over the last three to four years, a clear view of the association between the Big Five personality traits and video games may be achieved.